Anti‐inflammatory and anti‐chemotactic effects of dietary flaxseed oil on CD8+ T cell/adipocyte‐mediated cross‐talk. Issue 3 (29th December 2015) - Monk, Jennifer M.; Liddle, Danyelle M.; Brown, Morgan J.; Zarepoor, Leila; De Boer, Anna A.; Ma, David W. L.; Power, Krista A.; Robinson, Lindsay E.
Abstract : Scope: CD8 + T cell/adipocyte paracrine interactions represent a critical step in the development of the obese inflammatory phenotype that is disrupted by long‐chain n ‐3 PUFA. Our objective was to determine the effect of flaxseed‐derived n ‐3 PUFA (α‐linolenic acid) on these paracrine interactions. Methods and results: C57BL/6 mice were fed 3.5% flaxseed oil (FX) + 3.5% corn oil diet w/w or an isocaloric 7% corn oil w/w control diet (CON) for 3 wk. 3T3‐L1 adipocytes and purified primary splenic CD8 + T cells were cocultured at an obese cellular ratio (10% CD8 + T cells) and LPS‐stimulated (10 ng/mL mimicking obese circulating endotoxin levels) for 24 h. FX cocultures reduced (i) secreted IL‐6, tumor necrosis factor α (TNF‐α), macrophage chemoattractant protein 1 (MCP‐1), macrophage inflammatory protein 1α (MIP‐1α), and RANTES (regulated on activation, normal T cell expressed and secreted) levels; (ii) activation of inflammatory transcription factors NFκB (nuclear factor kappa‐light‐chain‐enhancer of activated B cell) p65 and signal transducer and activator of transcription‐3 (STAT3); and (iii) RAW264.7 macrophage chemotaxis versus CON ( p ≤ 0.05). Coculture of pre‐inflamed adipocytes (10 ng/mL LPS, 24 h prior to CD8 + T‐cell addition) resulted in reduced secretion of IL‐6, IL‐1β, MCP‐1, MCP‐3, MIP‐1β, and RANTES in FX cocultures versus CON ( p ≤ 0.05). Conclusion: FX exerts an anti‐chemotactic and anti‐inflammatory effect on CD8 + T cell/adipocyte paracrine interactions (cross‐talk), which has the potential to mitigate macrophage chemotaxis which drives components of the obese phenotype.